Interplay of structural, optical, and magnetic properties of Ce1-xNdxO2-δ nanoparticles with electronic structure probed using X-ray absorption spectroscopy. (October 2020) - Dave, Mridula; Kumar, Sudhish; Dalela, B.; Alvi, P.A.; Sharma, S.S.; Phase, D.M.; Gupta, M.; Kumar, Shalendra; Dalela, S.
Abstract: The CeO2-δ and Ce1-x Ndx O2-δ (x = 0.02, 0.04 and 0.06) nanoparticles, synthesized by microwave assisted co-precipitation method have been investigated for structural, optical, electronic structure and magnetic properties using X-ray diffraction, transmission electron microscopy, Absorption spectroscopy, surface enhanced Raman spectroscopy, X-ray absorption spectroscopy (XAS), and SQUID magnetometer. TEM and XRD measurements indicate face-centred cubic fluorite structure of CeO2 with Fm -3 m space group. The Raman spectroscopy indicates that all the Nd 3+ -doped CeO2 samples downward shifting of F2g band with introduction of oxygen vacancies. Further, band gap decrement has been observed with incorporation of Nd 3+ ions in CeO2 lattice. The XAS spectra of Ce M − edge clearly indicate changed valence state of Ce ions from Ce 4+ to Ce 3+ with Nd 3+ doping concentrations. The formation of oxygen vacancies is also confirmed with O K- and Nd M-edges XAS analysis. It is revealed that new complexes Ce 3+ -VO - Nd 3+ and Ce 4+ - VO –Ce 3+ have been introduced to support FM ordering through the development of F + -centres. Therefore, it can be concluded that oxygen vacancies play a prominent role in improving the ferromagnetic and various properties of these nanomaterials, to make them suitable for many applications as UV blocker, Photocatalyst, Spintronics and Optoelectronics applications. Highlights: Nd-doped CeO2 nanoparticles, synthesized using co-precipitation method. Characterization using XRD, Transmission Electron Microscopy, SQUID-VSM, Raman and X-ray Absorption Spectroscopy. XRD and Raman analysis confirms formation of face-centred cubic fluorite structure with Fm -3 m space group. Formation of oxygen vacancies in all samples, which is confirmed with O K-, Ce M − and Nd M-edges XAS analysis. Formation of Ce 3+ -Vo -Nd 3+ and Ce 4+ -Vo -Ce 3+ F-centres to give rise to Room Temperature Ferromagnetism in all samples.